MTB-MLE Classroom Interactions: A Pedagogical Analysis of Language Functions Among Meranaw Grade 1 - Lomangco, Sittie Hafsah (International Journal of Language and Literary Studies, 2025)
This naturalistic research was undertaken with the intention of analyzing the pedagogical linguistic functions of actual classroom interaction settings among Grade 1 students. It aimed to observe how MTB-MLE is actually used in classroom interactions, specifically among the multilingual Grade 1 Maranao students in Marawi City and Lanao del Sur. Employing an explanatory sequential mixed-methods design, classroom interactions were recorded and analyzed using the UAM Corpus Tool and Flanders’ Interaction Analysis Categories. These are broadly classified into two groups in this study: 1) Teacher-related categories — teacher asks questions, the teacher gives direction, the teacher criticizes, the teacher gives a lecture, and the teacher repeats the pupil’s answer verbatim, and 2) Pupil-related categories — pupil-talk response and pupil-talk initiation. Quantitative analysis revealed a prevalent teacher-dominated discourse, characterized by frequent questioning and directives, across both public and private schools. However, qualitative analysis revealed a stark contrast in MTB-MLE implementation: public schools predominantly used Meranaw, which fostered more student-initiated talk, while private schools heavily favored English. As these are both forms of positive reinforcement, which is the only popularly endorsed type of extrinsic motivation, the adequate attention or low valuation accorded them is deemed a loss for teachers who probably do not realize well enough the importance of motivation and the advantages accruing from the optimal use of this as a critical factor in the teaching-learning environment. These findings suggest that while teacher questioning remains a key pedagogical strategy, its dominance may limit student-initiated discourse. Furthermore, the variable implementation of MTB-MLE highlights challenges to policy uniformity, which may impact students’ linguistic development. The study underscores the potential of the mother tongue to foster engaging learning environments in public schools. Recommendations include a stronger mandate and support for the equitable implementation of MTB-MLE across all school types, comprehensive teacher training in multilingual pedagogy, the development of high-quality Meranaw-based resources, and the alignment of assessment practices with MTB-MLE principles. Further research is needed to explore the long-term impact on academic achievement and to investigate teacher language use patterns in more detail. This study contributes valuable insights into the micro-level dynamics of MTB-MLE implementation in a specific multilingual context, informing policy and practice for enhanced language education.